Antibiotic Resistance Trends in Uropathogens during the COVID-19 Pandemic in Western Romania: A Cross-Sectional Study - Elena Hogea; Alexandra Cristina Muntean; Felix Bratosin; Iulia Georgiana Bogdan; Oana Plavitu; Adelina Fratutu; Cristian Oancea; Mihai Calin Bica; Delia Muntean; Ingrid Hrubaru; Zoran Laurentiu Popa; Adrian Cosmin Ilie (MDPI AG, 2024)
The emergence and spread of antimicrobial resistance have been significant global health challenges, exacerbated by the COVID-19 pandemic. As healthcare systems faced unprecedented pressures, the management of non-COVID conditions, including urinary tract infections (UTIs), also encountered obstacles due to changes in microbial flora and antibiotic usage patterns. This cross-sectional study aimed to characterize the antimicrobial resistance trends among bacterial uropathogens isolated from patients in the Western region of Romania, between January 2020 and December 2022. The objectives were to map the resistance patterns and observe the pandemic's influence on antimicrobial resistance, particularly among enterobacterial Gram-negative species, to guide treatment and infection control strategies. From a total of 2472 urine samples collected during the study period, 378 positive samples were analyzed. This study found that Escherichia coli was the most commonly isolated uropathogen, making up 46.3% of the cases (n = 175), with Klebsiella pneumoniae at 20.6% (n = 78). There was a high resistance of Klebsiella pneumoniae to several antibiotics, while carbapenemase production increased to 52.5% and extended-spectrum beta-lactamase (ESBL) present in 24.3% of the strains. Escherichia coli showed high resistance rates to amoxicillin-clavulanic acid (from 45.4% in 2020 to 53.8% in 2022) and trimethoprim/sulfamethoxazole (from 27.5% in 2020 to 47.2% in 2022). The increasing trend of antimicrobial resistance noted during the pandemic, especially in Gram-negative enterobacterial species, highlights the urgent need for robust infection control measures and rational antibiotic use. This study underscores the critical importance of continuous surveillance to adapt antibiotic therapies effectively and prevent the further spread of resistance, thereby ensuring effective management of UTIs in the evolving healthcare landscape influenced by the pandemic.